Danmarks gamle Personnavne: En milepæl i dansk personnavneforskning - Eggert, Birgit (Danske Studier, 2016)
80 years ago, in 1936, the first part of the dictionary Danmarks gamle Personnavne (The old Personal names of Denmark) was published. It is a comprehensive work and a milestone in Danish personal name research. Every single name is followed by meticulous series of examples, and often the names’ etymology and origin are explained. The earliest examples of personal name research in Denmark date back to the 17th and 18th centuries, but it was not until the middle of the 19th century that what is regarded as modern research in personal names began. Subjects like first names in early times, foreign names in Denmark, local name use, calling after forefathers, bynames and surnames has been studied since then, and they are still of current interest. The last c. 50 years there has also been an increasing of interest for the Danish personal name researchers to investigate the contemporary name use, name trends, and social aspects in naming. Since the dictionary of the old personal names of Denmark was published, not many other investigations have been made with empiric material that covers the whole country and at the same time as meticulous, but it is indeed an example to follow whenever possible.